Biochemistry and Bioactive Compounds on Bamboo Shoots as the Main Component in Lumpia Semarang - Ainezzahira, Ainezzahira; Mudhita, Cynthia; Giovani, Ivana; Buntoni, Metta Santika; Magdasari, Junita (Fakultas Farmasi, Universitas Gadjah Mada, 2017)
Semarang style lumpia (or spring roll) is a typical culinary in Semarang city that uses bamboo shoots as filling. The objective of this study is to determine biochemical contents and bioactive compounds in bamboo shoots as the main filling component of Semarang Style Lumpia. This journal will discuss bamboo shoots in terms of the physical characteristics, chemistry, nutrition, sensory, bioactive compounds that exist in them. The result shows that bamboo shoots have physical characteristics, i.e soft texture, crunchy, and generally yellow. The chemical compositions of raw bamboo shoots per 100 grams are 2.6% of protein, 0.3% of fat, 5.2% of carbohydrate, and 91% of water. Bamboo-shoots are sources of food that have low fat but high fiber and minerals so bamboo shoot can be a source of healthy food. Bamboo shoots also contain 17 amino acids, 8 of which are essential for human body. The flavors found in bamboo shoots are influenced by total sugar content, amino acids, and tannins. In general, bamboo shoots have a spicy flavor that comes from cyanide. Bamboo-shoots contain some phytochemical groups that have roles for health, one of them is phenolic compounds. These compounds provide positive health effects such as anti-oxidants, anti-inflammatory, anti-allergy, and anti-microbial. The antioxidant type of phthiocerol on bamboo shoots can lower cholesterol and protect from free radicals.Â Keywords : Biochemistry, Bioactive, Characteristic, Semarang Style Lumpia, Bamboo Shoots.